The impacts of flood disasters on the poverty and income disparity in Malaysia: Fine-tuning the shared prosperity vision 2030 - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon Yew; Noor Amira Syazwani, Abd Rahman; Kong, Lai Kuan (Human Resource Management Academic Research Society (HRMARS), 2022)
Reducing the income gap among the people has been one of the main aspirations of the Malaysian government since long ago through public policies such as the New Economic Policy, National Development Policy, and so on. Efforts to reduce this income gap require a concerted effort between all parties including the people. However, climate change that has occurred drastically in recent times has caused frequent floods to hit the country and subsequently has a great impact, especially on the poor. Therefore, this study was conducted to discuss the impacts of flood disasters on poverty and income disparity in Malaysia. This study found that the poor are more severely affected by floods than the rich which further widens the income gap among the people. This will have an impact on the government's achievement in achieving the main objective of the Shared Prosperity Vision 2030 which focuses on reducing the income gap and improving the well-being of the people.